Business pivoting to domestic departure terminal of I Gusti Ngurah Rai Airport Bali for business sustainability - Ramadhani, Mohammad; Mussry, Jacky (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
PT Travelindo International (Travelindo) is a travel retail company that operates in the Bali airport. They operate in the international terminal of I Gusti Ngurah Rai Airport Bali. The problem is due to Covid-19 pandemic, the business drops as direct impact of travel restriction of international travelers to Bali and they would like to pivot their business to domestic departure terminal as business continuity plan. The company plan to pivoting their business to domestic departure terminal however they lack of knowledge on the customer profile there. To analyze and research this both quantitative and qualitative research methodology is used to gain information and alternatives of market segmentation that Travelindo could focus on. The primary data gathered from spreading online questionnaires and depth-interview with selected respondents. For analysis technique, K-mean clustering analysis is performed. To pivoting the business to domestic departure terminal, there are five market segments that Travelindo should focus on which consist of three market segments from buyers and two market segments from browsers. The important findings are the majority of the domestic travelers are having impulsive shopping behavior and their product type preference is souvenir.